The effectiveness of schema therapy with cognitive behavioral therapy on self-efficacy and quality of life in women with MS - Heidari, Maryam; Mami, Shahram; Ahmadi, Vahid; Khamooshian, Kianoosh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: According to people with MS, they have low quality of life and low self-efficacy. Therefore, this study was conducted with the aim of investigating self-efficacy and quality of life in women with MS. Methods: The current research was of applied purpose and in terms of methodology, it was quasi-experimental with a pre-test-post-test design, a control group and a two-month follow-up. The statistical population of the study included all women suffering from multiple sclerosis (MS) in Kermanshah during 2019-2020, who had referred to the Imam Reza Educational-Therapeutic Center. Using available and targeted sampling, 45 people were selected and randomly assigned to three groups (schema therapy = experimental group 1; cognitive behavioral therapy =experiment group 2 and control group). The data collection tool included the World Health Organization Quality of Life Questionnaire (1996) and Scherer and Maddox Self-Efficacy Questionnaire (1982). After determining and randomly placing the experimental and control groups, therapeutic interventions were applied to the experimental groups in the form of two sessions per week, each session lasting 1.5 hours. A week after the completion of the treatment sessions, the experimental and control groups were subjected to a post-test. Statistical analysis of data was done with SPSS version 25 software. Results: Data analysis using Variance analysis of repeated measures showed: Schema therapy and cognitive-behavioral therapy had a significant effect on the quality of life (F = 219.49, P = 0.001) and self-efficacy (F = 21.929, P = 0.001) of the research sample. Moreover, the significance of Bonferroni's post hoc test indicated the stability of the effects of both treatments. Conclusion: According to the results, it is suggested to the health policy makers to take cognitive-behavioral treatment measures and programs to improve the quality of life and self-efficacy of women with MS.